Species of Fruit Flies Attacking Citrus (Citrus sp.) and their Control using Various Attractants in Padang, West Sumatera, Indonesia - Hidrayani, Hidrayani; Yunisman, Yunisman; Tasari, Nurmelia; Ikhsan, Zahlul (AGRIVITA Journal of Agricultural Science, 2024)
Identification of fruit flies and the methods of their control are essential to overcome the problem of pests. Using attractants is one of the control methods, which is environmental friendly and leaves no residue on plants. The study aimed to identify the species of fruit flies attacking Siam citrus plants and determine the most effective type of attractants to control their population. Identification was made on the fruit flies captured on attractants, and the study on attractants was conducted using a Randomized Block Design (RBD) consisting of four treatments and five replications. Four treatments (type of attractants) were petrogenol, rongit glue, chery glue, and king super glue. Two species of fruit flies, i.e., Bactrocera dorsalis and B. umbrosa, were found in the citrus plantation in Lambung Bukik Padang. The most effective attractants to control the fruit fly population were rongit glue and super king glue, which trapped the highest number of flies. Rongit glue trapped on the average of 94.2 individuals, and King superglue at 91.0 individuals per week. Rongit glue and super king glue can reduce fruit fly attacks. It is also part of an integrated pest management system to support sustainable agriculture.